2006
DOI: 10.1177/003335490612100205
|View full text |Cite
|
Sign up to set email alerts
|

CDC Consultation on Methamphetamine Use and Sexual Risk Behavior for HIV/STD Infection: Summary and Suggestions

Abstract: In January 2005, the U.S. Centers for Disease Control and Prevention hosted a national consultation of scientists, public health officials, and community service providers to address growing concerns about the association of methamphetamine use and sexual risk behavior for HIV/STD infection, which is well documented among men who have sex with men. The purpose of the consultation was to review a representation of the current state of the science and practice on the topic in order to reduce the situational link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
66
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 20 publications
5
66
0
Order By: Relevance
“…In the high-risk behavior venues, our results are consistent with previous studies finding an association between STIs, including HIV, and methamphetamine/cocaine use among MSM and heterosexual men (CDC, 2006;Mansergh et al, 2006). Cocaine use and, in particular, crack cocaine, has been strongly associated with HIV high-risk behaviors, sex work, and STIs in various populations in the United States (Compton et al, 1995) and also among Latino immigrants (Paz-Bailey, Teran, Levine, & Markowitz, 2004).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the high-risk behavior venues, our results are consistent with previous studies finding an association between STIs, including HIV, and methamphetamine/cocaine use among MSM and heterosexual men (CDC, 2006;Mansergh et al, 2006). Cocaine use and, in particular, crack cocaine, has been strongly associated with HIV high-risk behaviors, sex work, and STIs in various populations in the United States (Compton et al, 1995) and also among Latino immigrants (Paz-Bailey, Teran, Levine, & Markowitz, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…Over time, environmental and behavioral factors may increase the opportunities for HIV-infected individuals to enter into Latino migrant sexual networks, and migrant communities could experience higher rates of HIV infection and transmission (Apostolopoulos et al, 2006;Rangel et al, 2006;Worby & Organista, 2007). Methamphetamine and cocaine use promotes opportunities for becoming infected with HIV and sexually transmitted infections (STIs) among men who have sex with men (MSM) and, more recently, among men who have sex with women, particularly through unprotected anal and vaginal intercourse and unprotected intercourse with a new partner (Centers for Disease Control and Prevention [CDC], 2006;Compton, Lamb, & Fletcher, 1995;Mansergh et al, 2006;Molitor, Truax, Ruiz, & Sun, 1998;Zule, Costenbader, Meyer, & Wechsberg, 2007). Although there is evidence that methamphetamine and crack cocaine smoking is increasing nationally, especially in the border states in Mexico and in the United States, in addition to increasing non-injected methamphetamine use among Latinos diagnosed with AIDS in California, research is scarce addressing these behaviors among Mexican migrants in relation to HIV (Maxwell et al, 2006;Rock Wohl, Johnson, & Frye, 2007).…”
mentioning
confidence: 99%
“…Reports of four major U.S. cities found 9.5% of MSM reported methamphatimine use within the past 6 months [15]. When erectile dysfunction drugs such as Viagra are combined with methamphetamine use, unprotected anal intercourse increases [16]. Methamphet-amine use also contributes to increased frequency of sex, greater number of sex partners, and engagement in sex marathons [2].…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale, coordinated anti-methamphetamine campaigns have been implemented in metropolitan areas outside of the Southern U.S. [23,24]. However, with the exception of Nanin and his colleagues' findings that public health antimethamphetamine initiatives in New York City were successful in reaching recent sexual at-risk MSM methamphetamine users [24], there has been minimal evaluation of these community campaigns to date.The U.S. Centers for Disease Control and Prevention (CDC) hosted a national consultation in 2005 on the issue of methamphetamine use and sexual risk for HIV and other sexually-transmitted infections [25]. At this event, the state of the relevant science was summarized, ongoing programs were reviewed, and existing needs related to methamphetamine research and community programming were identified.…”
mentioning
confidence: 99%